Enhancing Student Learning Outcomes Through Contextual Teaching and Learning in Science at Al Fattah Bungo - Saiful Azizi Nik Abdullah, Nik Md; Shohib, Muhammad Wildan (Yayasan Lembaga Studi Makwa, 2025)
This study aims to determine the improvement of student learning outcomes through the application of the Contextual Teaching and Learning (CTL) model in the subject of Natural Sciences, specifically simple machines, at the Madrasah Tsanawiyah level of Al Fattah Sungai Binjai Islamic Boarding School, Bungo Regency. The research was motivated by initial observations showing that mastery of simple machines material was below the minimum competency standard (KKM), with a completion percentage of only 25%. The purpose of this study is to improve students’ critical thinking, practical skills, and interest in science and technology by implementing the CTL approach. The research design employed Classroom Action Research (CAR) with two cycles. Data collection techniques included tests, observations, interviews, and documentation. Data analysis used both qualitative and quantitative approaches to evaluate changes in cognitive, affective, and psychomotor aspects. The findings revealed significant improvements in student learning outcomes. In cycle I, the cognitive aspect reached 46.42%, the affective aspect 52.85%, and the psychomotor aspect 52.51%. In cycle II, these outcomes increased to 80% for the cognitive aspect, 80.08% for the affective aspect, and 80.93% for the psychomotor aspect. The implications of this research suggest that the CTL model can effectively enhance learning outcomes in science, particularly in the topic of simple machines, and serve as a valuable strategy to support student readiness for future scientific and technological challenges.